2017
DOI: 10.7717/peerj.3918
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study: does upper airway morphology differ between non-positional and positional obstructive sleep apnea?

Abstract: ObjectiveThe objective of this study was to explore the differences in upper airway morphology between positional (POSA) and non-positional (NPOSA) obstructive sleep apnea.MethodsThis retrospective study enrolled 75 patients (45 NPOSA and 30 POSA) who underwent polysomnography (PSG) and computed tomography (CT). The differences in, and relationships of, the PSG values and CT data between POSA and NPOSA were analyzed.ResultsSignificant (p < 0.05) differences between the two groups were found in the apnea/hypopn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The increase in AHI-LAT was over twelve times greater in PPs who converted to NPPs compared to those who stayed as PPs. Furthermore, a recent Asian study comparing the upper airway morphology of PPs to that of NPPs supports the idea that AHI-LAT is a sensitive parameter describing OSA positionality 22 . The authors found that in NPPs the coronal diameter of the upper airway is smaller and the soft palate is longer compared to PPs.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The increase in AHI-LAT was over twelve times greater in PPs who converted to NPPs compared to those who stayed as PPs. Furthermore, a recent Asian study comparing the upper airway morphology of PPs to that of NPPs supports the idea that AHI-LAT is a sensitive parameter describing OSA positionality 22 . The authors found that in NPPs the coronal diameter of the upper airway is smaller and the soft palate is longer compared to PPs.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the AHI-LAT was associated with soft palate length. More the length of the soft palate exceeded 35.4 mm, the greater was the risk to become NPP 22 . Since the increase in the length of soft palate is most probably related, at least partially, to weight gain, these results also support the modulatory effect of weight change on positional OSA 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spearman correlation analysis revealed There is a statistically significant negative correlation between allergic rhinitis score and POSA (Spearman coefficient of r = -0,40; p < 0,0001) as well as a positive correlation between the apnea-hypopnea index and body mass index (Pearson coefficient of r = 0,32; p < 0,05). The result from a comparative retrospective study of 30 POSA and 45 non-POSA patients by means of polysomnography and computed tomography demonstrate statistically significant differences (p < 0,05) between both groups in terms of the apneahypopnea index, lateral apnea-hypopnea index, soft palate length, cross-sectional palatopharyngeal area, and coronal diameter of the palatopharyngeal area at the narrowest glossopharyngeal part (13). Only the apnea-hypopnea index, lateral apneahypopnea index and soft palate length values are lower in POSA patients.…”
Section: Diagnosis Of Posamentioning
confidence: 92%
“…However, only a few studies have compared craniofacial structures between POSA and NPOSA groups. Two studies have suggested that patients with POSA may have a smaller lower facial height, more backward positioned mandible, and shorter soft palatal length than patients with NPOSA [ 13 , 14 ]. However, Saigusa et al [ 14 ] found no significant difference in the anatomical balance of the upper airway between the POSA and NPOSA groups in their study.…”
Section: Introductionmentioning
confidence: 99%